Analisis Wacana Kritis Sebagai Refleksi Terbalik Perilaku Negatif Pada Tayangan Youtube - Istiani, Ade Nur; Widhiyatmoko, Yosep Yogo (Universitas Islam Negeri Raden Intan Lampung, 2020)
The development of digital information technology in recent times has presented many platforms that can be a source of information as well as a means of entertainment for the public. One of the new media that is popular with the public is YouTube. A platform that has given birth to many content creators with various genre of impressions. And the position of the community as a media audience in this situation is the party affected by the YouTube content, both positive and negative impressions. Based on this phenomenon, this media and cultural study is carried out in order to obtain what educational content looks like, by examining the signs of communication messages containing character building in the content of Berburu Mobil Impian. The study was conducted using a critical discourse analysis method with representation theory through a descriptive qualitative approach in translating the character education values that exist in the research object. The results of the study show that there are manifestations of character values and positive cultural values that are educational and inspiring, especially for young people, presented in their entirety and lightly but do not eliminate the element of entertainment in them. These signs can serve as role models for other content creators to create watch-worthy impressions. It also provides a reference for displaying content that is suitable for production and is healthy for audiences, especially young people, to access. The results of the study from the perspective of communication science are expected to contribute thoughts to the audience to be more sensitive to negative content on YouTube.